Distribution of recent ostracoda in offshore Sediment of selected stations in the Sulu Sea, Sabah - Noraswana, N.F.; Ramlan, O.; Norashikin, S. (Penerbit Universiti Kebangsaan Malaysia, 2014)
A study on the distribution of recent ostracoda in offshore sediment was carried out around the Sulu Sea, in Sabah Malaysia. Sediment samples were taken from 12 sampling stations ranging in depth from 24 m to 205 m. Environmental parameters including water depths, salinity, temperature, dissolved oxygen, total organic matter and grain size were measured and their relationship with the distribution of recent ostracoda are discussed. From this study, a total of 32 species of ostracoda from 14 families and 22 genera were successfully identified. The dominant species was Phlyctenophora orientalis with 449 specimens. The number of species ranged from 3 to 19. Index of Diversity, H(s) value, was from 0.9 to 2.8. The abundance and diversity of ostracoda are principally controlled by the depth factor. A correlation analysis showed that depth is positively correlated (r = 0.588, p < 0.05) with Index of Diversity, H(s). Other parameters do not show any significant correlation.